Urban Regimes of Dispossession in the Global South : A New Debate - Brunsma, David L.,; Mondal, Lipon, (Social Sciences E-Books Online, Collection 2026., 2025)
This edited volume develops a theoretical framework-what we call urban regimes of dispossession -for understanding how urban actors organize dispossession and govern the urban dispossessed, how the urban dispossessed arrange, experience and resist dispossession, and how urban dispossession contributes to creating/expanding capitalist systems or transforming urban societies in the global south. The book's main arguments are built on a survey of the nearly two-hundred-year history of global dispossession studies and solid empirical evidence from three continents-Asia, Africa, and Latin America, and seven countries- Bangladesh, Brazil, Honduras, India, Lebanon, Nigeria, and Uganda. Eighteen scholars bring diverse perspectives and realities on urban dispossession, which will appeal to students, scholars, planners, and practitioners across various social scientific disciplines, including sociology, anthropology, urban studies, political economy, international relations, political science, economics, gender studies, and geography. Contributors are: Shapan Adnan, Orlando Alves dos Santos Junior, Fred Bidandi, David L. Brunsma, Tarcyla Fidalgo Ribeiro, Lakshmi Jahnavi, Marie Kolling, Ana Maria Kumarasamy, Barbara Lipietz, Lipon Mondal, Adrian Murray, John Nagle, Victor Udemezue Onyebueke, Taísa Sanches, Karen Spring, Susan Spronk, Luanda Vannuchi and Julian Walker.